Sharia Economic Dispute Resolution: Analysis of the Decision of the Sekayu Religious Court - Lendrawati Lendrawati; Ibnu Amin; Faisal Efendi; Muhammad Khairi; Ys Tenra Septu Amin (Journal of Islamic Economics and Finance Studies, 2026)
Settlement of sharia economic disputes analysis of the decision of the Sekayu Religious Court Number 1/Pdt.G.S/2024/PA. Sky, this study aims to elaborate on the process of resolving sharia economic disputes by the Religious Court. This research is a normative legal research using case studies and library research presented descriptively with. The data was collected using the decisions of the Religious Court and literature, books, and scientific journals. This study shows that the settlement of sharia economic disputes between the plaintiff and defendants I and II in the mudharabah contract is the absolute authority of the Sekayu Religious Court. There are several findings in this study: 1) the mudharabah contract carried out by the plaintiff and defendant I is valid because it has met the requirements of the contract in the Compilation of Sharia Economic Law. 2) there was an admission of negligence by defendant I in the form of a promise to fulfill the elements of granting the plaintiff's lawsuit to defendants I and II. 3) The mudharabah contract carried out between individuals is valid when the pillars and conditions stipulated in the fiqh muamalah are met3) The mudharabah contract carried out between individuals is valid when the pillars and conditions stipulated in the fiqh muamalah are met.